A systematic review of the theory of mind studies and the potential for replications in linguistics / Siti Auji Ashari - Ashari, Siti Auji (Universiti Teknologi MARA, 2022)
The theory of mind is a psychological concept that refers to the awareness of one's mental states and others'. In the seminal study by Kidd and Castano (2013), the researchers found that reading literary fiction led to better performance in the theory of mind test relative to reading popular fiction, nonfiction, or reading nothing at all. This paper collates seven subsequent replications of the original study: five direct replications and two indirect ones using other media, namely the visual narrative of television and movies. The findings of these replications are then compared to the orig-inal findings in terms of whether they successfully replicated the results. After that, key differences between the gen-res of the media used in the original study and its replications are elaborated, namely the writerly and readerly texts. For discussion, this paper further argues the case for replicating the original study in linguistics. This paper explores two main points pertaining to second language acquisition and emotions. The first one is that the original study and its replications were carried out exclusively with native speakers of English. Accordingly, this necessitates replicating the original study with participants other than the first speakers. Meanwhile, considering the call for more replications, this paper makes the argument that since songs are short and elicit emotions, they present another viable medium for indirect replications.